Ideas map for the transformation of IFLA’s strategy - Pérez-Salmerón, Glí²ria (Anuario ThinkEPI, 2018)
This is the report of the International Federation of Libraries Associations and Institutions (IFLA) 2017-2019 President´s Program. It is the narrative of the presidential program based on the Ideas Map inspired by an exhaustive analysis of how IFLA is developing in accordance with its strategic plan 2016- 2021. The activities that IFLA has recently started are focused on this new approach, taking advantage of the opportunity of transformation that has been provided by the Bill & Melinda Gates Foundation, Global Libraries Legacy. I also discuss the needs that I have identified and I consider necessary to fulfil the expectations defined in my presidential theme: Libraries: motors of change.